A "turn-on" fluorescence platform of detection glutathione using MnO2 nanosheets quenched fluorescent conjugated polymer nanoparticles. (May 2020) - Wang, Qiu-bo; Zhang, Cui-jiao; Lu, Qian; Liu, Zhao-e; Yao, Jin-shui; Zhang, Xian
Abstract: Glutathione (GSH) plays an important role in the normal physiological activities of human body. It is significant to establish a simple and rapid analysis method to detect accurately GSH. In this work, a "turn-on" fluorescence platform based on conjugated polymer nanoparticles (CPNs) and MnO2 nanosheets was constructed for quantitative detection of GSH. The polymer of PBEC (poly [3-{2, 5-bis (2-ethyl-hexyloxy)}-phenyl]-vinyl]-9-ethyl-carbazole]) designed by our group, was co-precipitated to prepare the conjugated polymer nanoparticles (CPNsPBEC ). Combined with MnO2 nanosheets through van der waals force, a novel CPNsPBEC -MnO2 nano-platform was established based on the fluorescence resonance energy transfer (FRET). The fluorescence of CPNsPBEC will be recovered in the presence of GSH because the MnO2 nanosheets were reduced to Mn 2+, so the detection of GSH was realized. A limit of detection (LOD) of CPNsPBEC -MnO2 nano-platform is 20.4 nM. Furthermore, this nano-platform with high selectivity and sensitivity was applied successfully to the determination of GSH in mouse serum and plasma. All of these indicated that the nano-platform could be used to effectively monitor GSH and expected to achieve early diagnosis of GSH-related diseases. Graphical abstract: Image 1 Highlights: A novel sensing platform was constructed based on CPNsPBEC and MnO2 nanosheets. CPNsPBEC -MnO2 nano-platform was highly sensitive to GSH with a lower detection limit of 20.4 nM. CPNsPBEC -MnO2 nano-platform detected successfully GSH in actual samples (mouse serum and plasma).